Analysis of Liberal Feminism According to Naomi Wolf in the Novel Al Ajnihah Al Mutakassirah by Kahlil Gibran - Dimas Andrisesar Winarsoputra; Iin Suryaningsih; Sayyed Zuhdi Abdil Ghany (Jurnal Indonesia Sosial Teknologi, 2024)
Since ancient times, injustice in social life related to gender has become a frequent problem in society. Women are only objects and do not get equal rights in social life, education, and position before the law. Kahlil Gibran, a writer of the Mahjar Era from Lebanon, in the novel المتكسرة الأجنحة Al Ajnihah Al Mutakassirah (Broken Wings), raises the issue of women's helplessness against the influence of male power at that time. The character of Salma Karamy, the daughter of Faris Affandi, a wealthy man in Lebanon, is helpless in the face of the influence of the power of Bishop Bolus Galib who wants Faris's wealth by forcing the marriage of his nephew Mansour Bey Galib to Salma. Salma and Kahlil Gibran's love ran aground. This journal uses a qualitative-descriptive method to examine the novel المتكسرة الأجنحة Al Ajnihah Al Mutakassirah (Broken Wings) by Kahlil Gibran, in terms of feminism, especially liberal feminism according to Naomi Wolf. From the results of research and analysis of the novel الأجنحة المتكسرة Al Ajnihah Al Mutakassirah (Broken Wings) by Kahlil Gibran, it was found that the influence of religious leaders (Bishop Bolus Galib) was very large in social life in society. Women at that time lived oppressed, only as objects, and did not have equal rights with men. "A woman is like a commodity that is bought, offered, and moved from one house to another, then she will become like a piece of old furniture placed in a corner of darkness".